Algerian national library manuscripts: between the necessity of conservation and the need for communication - HASSENA, Ourdia (Journal of Human Sciences, 2020)
Digitization has considerably grown in the last two decades, with many libraries holding heritage funds, becoming more involved in digitization projects. These commitments undoubtedly meet the imperatives of conservation of collections on the one hand, and communication needs expressed by researchers on the other. In addition, the interest raised by these manuscripts on the national and international level, led the Algerian National Library to review its policy of conservation and preservation of its manuscripts. This work will essentially touch on three fundamental issues, namely the conservation of manuscripts, their communication and finally, digitization as a technological alternative that allows the production of digital copies of substitution more communicable, while ensuring the preservation of original copies.